PRE-SERVICE ENGLISH TEACHERS’ PERCEPTION ON TPACK AND THEIR TECHNOSTRESS DURING TEACHING INTERNSHIP - Faden, Griseldis (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2024)
This research aims to find out the correlation between pre-service English teachers’ perception on TPACK and their technostress during teaching internship especially pre-service English teacher in Islamic higher education. The participants of this research were 83 pre-service English teacher of English Education Department study program of IAIN Kediri who took part in teaching internships. This research use correlation method in analyzing and describing the pre-service English teachers’ perception on TPACK and their technostress. The instruments used to collect the data were the questionnaires of perception on TPACK and technostress. The result of this research was found that there is low correlation between pre-service English teachers’ perception on TPACK and their technostress during their teaching internship period with Pearson correlation coefficient 0.261 as evidenced by Sig. value is 0.017.